Penerapan metode diskusi untuk meningkatkan hasil belajar siswa kelas IV SDN Pajang IV - Tambunan, Rifka Paulina; Riyadi, Riyadi (Universitas Sebelas Maret, 2024)
This research aims to improve the learning outcomes of Civic Education Learning (PPKn) for grade IV students of SDN Pajang IV Surakarta by applying the discussion method. The subjects of this research are grade IV students of SDN Pajang IV, consisting of 13 boys and 11 girls. This research is a Classroom Action Research (PTK). The implementation of this research consists of 2 cycles, which include the preparation, implementation, observation, and reflection stages. Data collection techniques in this study were carried out through observation, interviews, and tests. The research results obtained show that the application of the discussion method can improve student learning outcomes. The implementation of cycle I to cycle II has experienced an increase. From the results of this study, it can be concluded that the application of the discussion method can improve the learning outcomes of grade IV students of SDN Pajang IV Surakarta